The Effect of Emotion and Spiritual Intelligence to Teacher’s Work Achievement in the Holy Christian School (SKKK) Bandung - Thinna Naftali Woenardi; H. Haris Supratno; Mudjito Mudjito (Budapest International Research and Critics University, 2022)
This research was conducted at Kalam Kudus Christian School (SKKK) Bandung to know the influence of emotional intelligence (X1) and spiritual (X2) on teacher’s work performance (Y1) at SKKK junior high school institution of Bandung. Factor factor of this background is low teacher performance, source of renewal of faith and low character, teachers often complain with work load as profession given by head of institute This research uses questioner with likertscala(summaratedratin score) to capture variable data X1 and X2. Population of 60 teachers, by taking 30 teachers with random sampling, reliability with the formula Cronbach Alpha, validity with the orthogonal iteation formula on the continuum data scale. The results of this research are first there is signification between teacher's emotional intelligence with work restriction found Ry1 equal to 0.58 is positive, t equal to 3,803 is signification at α <0,05 and F equal to 14,464 is significant at α <0,05. Secondly there is significant teacher's spiritual intelligence to teacher's work performance with found ry2 equal to 0,446 and t equal 2,638 significant α <0,05 with result F equal to 6,958. This research provides information to all educational staff, teachers and principals in the region of Bandung and Indonesia generally the importance of building and developing positive emotional and spiritual performance of teachers in an effort to improve education services.